PENERAPAN PEMBERDAYAAN BERPIKIR MELALUI PERTANYAAN (PBMP) DALAM PEMBELAJARAN AKTIF TIPE TEAM QUIS UNTUK MENINGKATKAN HASIL BELAJAR FISIKA SISWA DI SMPN 2 BATULAYAR - Syifaul Gummah; Saiful Prayogi; Sukainil Ahzan; Islamiyah Islamiyah (Lensa: Jurnal Kependidikan Fisika, 2014)
This study aims to improve the learning achievement of Physics science through the application of Empowering thinking Using Questions (PBMP) In Active Learning 'Team Quis Type for Students in Secondary School. The type of research is classroom action research conducted in two cycles consisting of: planning, implementation, observation and evaluation phase, and reflection. Activity data for students and teachers is obtained through the observation sheet, while the student learning result data is obtained through the test given at each end of the cycle. The indicator of the success of the research is the students are categorized as active and have increased. Student learning achievement is completed in a classical manner where the students who scored ≥ KKM 75 score has reached ≥ 85% based on the total number of students who follow the evaluation test. Students' physics learning achievement in the first cycle obtained the average grade of 73.8, classical completeness 75.0%, and the average value of student learning activities of 12.3 who are in the category quite active. In the second cycle obtained an average score of 80.2 with 85.0% classical completeness, and the average value of student learning activities of 17.0 are in the active category. We conclude that PBMP has been able to improve students' physics learning outcomes.